Optimization of Village Office Services through Service Standards, Complaint Services, and Community Satisfaction Surveys - Mathory, Eljihad Akbari Syukriah; Ramdhani, Arindah Mutiara; Reston, Rhegyna Vanessa; Nurjannah, Miftahul (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
This community service aims to improve the quality of public services in Coppo Tompong Village, Mandalle District, Pangkajene and Islands Regency, with a focus on complaints, community satisfaction surveys, and service standards. The method used in this community service uses the PAR method. In the PAR method, the community becomes a collaborative partner, not an object of research. The PAR method has several principles, including the principles of participation, action orientation, triangulation, and flexibility. The results of initial observations showed several problems, including complaints services that were still manual, the absence of service standards, and no forum for assessing community satisfaction. The solutions carried out were the creation of a Google Form-based complaint service, the preparation of service standard documents, and the creation of a community satisfaction survey. The community satisfaction survey conducted aims to measure how satisfied the community is with the services received, with the survey results showing that services at the Coppo Tompong Village Office fall into the "Very Good" category with the results of the Community Satisfaction Index value showing a value of 90.63. In addition, an infographic of the survey results and service standards was created which can be accessed through Linktree. Despite obstacles such as limited technological knowledge among the community, this service is considered successful in improving the transparency and efficiency of public services in the village, as well as providing long-term benefits for villagers.